THE INFLUENCE OF COMPENSATION AND JOB STRESS ON THE PERFORMANCE OF CIVIL SERVANTS IN THE HEALTH SERVICES - Nur Aurellia Marta Lerifka Maharani; Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2024)
Purpose: The purpose of this study is to investigate the partial and simultaneous impact of compensation and job stress on the performance of ASN employees at Karawang Health Service. Research Methodology: This study uses a descriptive verification approach with a quantitative approach, using a questionnaire as a survey instrument. The sample consisted of 81 employees, selected according to the Slovin formula. The analysis was performed using a multiple regression model. Results: The results of the study show that compensation has a partial positive effect on employee performance, job stress also has a partial positive effect on employee performance, and that compensation and job stress have a simultaneous positive effect on employee performance in Karawang Health Service. Limitations: The study was conducted only at the Karawang Health Service, and the variables analyzed were limited to compensation and job stress. Future studies could expand the scope and include additional variables. Contribution: This study provides insights for the Karawang Health Service on the importance of managing compensation and job stress to improve employee performance. The findings can be used as a reference for other government agencies to enhance the performance of their employees.